(untitled) (Transport systems and technologies, 2021)
The article deals with the main existing strategies for management strategy of energy exchange processes in the electric rolling stock with onboard capacitive energy storage devices. When considering strategies, it is assumed that the onboard capacitive storage has low power and capacitance. Therefore, this capacitor storage is not able to accept the full amount of regenerative braking energy of the electric rolling stock. The purpose of the paper is to consider and analyze management strategies for energy exchange processes in the electric rolling stock with onboard capacitive energy storages; to define the advantages and disadvantages of each of the existing strategies and propose a concept for the effective management of energy exchange processes in the electric rolling stock. The block diagram of electric rolling stock with the onboard capacitive energy storage which is used for the analysis of management strategies for energy exchange processes is presented. The modes of operation of electric rolling stock with onboard capacitive energy storages are described. Five main strategies for management of energy exchange processes on the electric rolling stock with onboard capacitive energy storages are determined. The advantages and disadvantages of each strategy are set out taking into account the given conditions (characteristics of the electric rolling stock, conditions of the rolling stock motion, oscillograph charts, etc.). The general advantages and shortcomings of each strategy are defined, which allowed to propose the concept of creating an adaptive strategy for managing energy exchange processes in electric rolling stock with onboard capacitive energy storages. The main concept of this management strategy is to implement efficient energy exchange between the traction equipment, the onboard capacitive energy storage, the overhead contact system, both in normal and emergency modes of traction power supply, taking into account the dynamics of energy exchange processes in the overhead contact system, which will generally allow safety and energy efficiency of the transportation process. The obtained research results will contribute to the development and implementation of effective strategies for managing energy exchange processes in the electric rolling stock.